2017
DOI: 10.1038/s41598-017-17896-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripersonal space representation develops independently from visual experience

Abstract: Our daily-life actions are typically driven by vision. When acting upon an object, we need to represent its visual features (e.g. shape, orientation, etc.) and to map them into our own peripersonal space. But what happens with people who have never had any visual experience? How can they map object features into their own peripersonal space? Do they do it differently from sighted agents? To tackle these questions, we carried out a series of behavioral experiments in sighted and congenitally blind subjects. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Serino and collaborators’ study 60 cited above indeed illustrated that blind people displayed more permanent changes than blindfolded sighted participants in their peripersonal space representation. Quite interestingly, it seems that congenitally blind participants can remap objects in their peripersonal space, or in others’ peripersonal space as well as sighted participants 61 , reinforcing the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Serino and collaborators’ study 60 cited above indeed illustrated that blind people displayed more permanent changes than blindfolded sighted participants in their peripersonal space representation. Quite interestingly, it seems that congenitally blind participants can remap objects in their peripersonal space, or in others’ peripersonal space as well as sighted participants 61 , reinforcing the need for further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioral studies of neurological patients as well as neuroimaging studies employing functional magnetic resonance imaging (fMRI) and transcranial magnetic stimulation (TMS) with healthy participants demonstrated that humans also maintain populations of neurons, located within the intraparietal sulcus (IPS), supramarginal gyrus (SMG), and regions of the premotor cortex, that selectively represent the space near the body (Berti & Frassinetti, 2000;Brozzoli, Ehrsson, & Farnè, 2014;Cowey, Small, & Ellis, 1994;Ferri et al, 2015;Serino, Canzoneri, & Avenanti, 2011; for reviews, see Cléry et al, 2015;Grivaz, Blanke, & Serino, 2017). Much evidence also suggests that representations of PPS in humans, like those of the macaque monkey, are multimodal in nature, responding to visual (Longo & Lourenco, 2006), visuo-tactile (Noel, Pfeiffer, Blanke, & Serino, 2015;Serino et al, 2015), and audio-tactile (Canzoneri, Magosso, & Serino, 2012;Ricciardi et al, 2017) information (for review, see Van der Stoep et al, 2015). Moreover, and crucially, as in the monkey, these representations in humans appear to be body-part-centered, such that bodily dimensions influence the size of PPS.…”
Section: The Non-defensive Functionmentioning
confidence: 99%
“…Similarly, multisensory space near the body (peripersonal space) has been shown to be influenced by (lack of) early visual experience (Collignon, Charbonneau, Lassonde & Lepore, 2009; but see also : Ricciardi et al, 2017). Thus, there are indications that multisensory integration mechanisms are altered in blind individuals, although very little is known about such changes in the integration process responsible for the perception of their own bodies.…”
Section: Introductionmentioning
confidence: 99%